Pengaruh Tingkat Pendidikan Dan Lingkungan Kerja Fisik Terhadap Kinerja Pegawai Pada Disdukcapil Kota Tangerang Selatan - Muhammad Tegar Satria; R.A Kadarmanta (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study is to determine the effect of Education Level and Physical Work Environment on Employee Performance at the Department of Population and Civil Registration (DISDUKCAPIL) of South Tangerang City, both partially and simultaneously. The research method used is a quantitative method with an associative research type.The results of the t-test show that the Education Level has a significant effect on Employee Performance, with a significance value of 0.001 < 0.05 and a t-value of 7.904 > t-table of 1.987. Meanwhile, the Physical Work Environment has no significant effect on Employee Performance, with a significance value of 0.398 > 0.05 and a t-value of |0.849| < t-table of 1.987.The results of the F-test indicate that Education Level and Physical Work Environment simultaneously have a positive and significant effect on Employee Performance, with a significance value of 0.001 < 0.05 and an F-value of 61.363 > F-table of 3.10.The results of the Coefficient of Determination (Adjusted R-Square) test show a value of 0.576 or 57.6%, which means that simultaneously the influence of Education Level and Physical Work Environment on Employee Performance contributes 57.6%, while the remaining 42.4% is influenced by other variables outside this research model.